The Impact of Ethnic Subgroups on Tumor Stage at Diagnosis, Treatment Received, and Long-Term Survival Among Asian Adults With Hepatocellular Carcinoma - Yu, Justin R. (J Clin Exp Hepatol, 2019)
BACKGROUND & AIMS: Hepatocellular carcinoma (HCC) outcomes among Asians may differ by the Asian ethnic subgroup. We aim to evaluate the impact of the Asian ethnic subgroup on HCC tumor stage, treatment received, and overall survival among US adults. METHODS: Using the 2004–2012 Surveillance, Epidemiology, and End Results U.S. cancer registry, we retrospectively evaluated disparities in HCC tumor stage at diagnosis, HCC treatment received, and overall survival among Asian adults, stratified by Asian ethnic subgroups. Multivariate regression models evaluated the independent impact of Asian ethnic subgroups on the HCC tumor stage at diagnosis, treatment received, and overall long-term survival. RESULTS: Among 8160 Asians with HCC, Southeast Asian (SEA) patients accounted for 26% of all HCC, followed by Chinese (CH) (22%), and Filipinos (FP) (14.0%) patients. Japanese (JP) patients were significantly older than those of the other subgroups (mean 71.1, SD 10.8, P < 0.01). When evaluating HCC stage, FP patients were less likely to have localized HCC and less likely to have HCC within the Milan criteria than CH HCC patients. When evaluating HCC treatment, pacific islanders (PI), FP and SEA patients were significantly less likely to any receive HCC treatment than CH patients. Overall five-year HCC survival was highest among CH HCC patients (33.1%) and lowest among FP (19.9%) and JP patients (22.0%). CONCLUSION: Among Asians with HCC in the US, significant disparities among Asian ethnic subgroups exist. More advanced disease was seen among FP patients, less HCC treatment was seen among FP and SEA patients, and significantly higher mortality was seen among FP, SEA, and JP patients with HCC.